Fifth Chinese National Consensus Report on the management of Helicobacter pylori infection - Liu, Wen Zhong; Xie, Yong; Lu, Hong; Cheng, Hong; Zeng, Zhi Rong; Zhou, Li Ya; Chen, Ye; Wang, Jiang Bin; Du, Yi Qi; Lu, Nong Hua (Helicobacter (Cambridge, Mass.), 2018)
Background Since the ‘Fourth Chinese National Consensus Report on the management of H. pylori infection’ was published in 2012, three important consensuses (Kyoto global consensus report on H. pylori gastritis, The Toronto Consensus for the Treatment of H. pylori Infection in Adults and Management of H. pylori infection—the Maastricht V/Florence Consensus Report) have been published regarding the management of H. pylori infection. Materials and Methods A Delphi method was adopted to develop the consensus of relevant ‘statements’. First, the established ‘statements’ were sent to experts via email. Second, after undergoing two rounds of consultation, the initial statements were discussed face to face and revised in the conference item by item on 16 December 2016. Finally, 21 core members of conferees participated in the final vote of statements. Voting for each statement was performed using an electronic system with levels of agreements shown on the screen in real time. Results Consensus contents contained a total of 48 “statements” and related 6 parts, including indications for H. pylori eradication, diagnosis, treatment, H. pylori and gastric cancer, H. pylori infection in special populations, H. pylori and gastrointestinal microbiota. Conclusions Recommendations are provided on the basis of the best available evidence.